2017
DOI: 10.1159/000479722
|View full text |Cite
|
Sign up to set email alerts
|

Complete Regrowth of Beard Hair with Ruxolitinib in an Alopecia Universalis Patient

Abstract: While most alopecia areata (AA) cases resolve spontaneously, the more severe types of AA, alopecia totalis (AT) and alopecia universalis (AU), can be highly resistant to therapy. We report on a 33-year-old ultraorthodox Jewish man with an 11-year history of AA that resulted in complete loss of the scalp and body hair 7 years ago. Previous treatments with intralesional and systemic corticosteroids had only partial and temporary effects. The patient was treated with ruxolitinib, 20 mg twice daily, resulting in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Other associated conditions with alopecia areata include atopic dermatitis, celiac disease, pernicious anemia, psoriasis, rheumatoid arthritis, systemic lupus erythematosus, and vitiligo [3,4]. Multiple therapies have been identified as effective treatments for beard alopecia areata ( Table 1) [3][4][5][6][7][8][9][10][11][12][13][14]. Treatment with corticosteroids (either intralesional or topical) is usually the first line of therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other associated conditions with alopecia areata include atopic dermatitis, celiac disease, pernicious anemia, psoriasis, rheumatoid arthritis, systemic lupus erythematosus, and vitiligo [3,4]. Multiple therapies have been identified as effective treatments for beard alopecia areata ( Table 1) [3][4][5][6][7][8][9][10][11][12][13][14]. Treatment with corticosteroids (either intralesional or topical) is usually the first line of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppressants [5,7], CR Corticosteroids (intralesional injections, topical) [5,7], CR Immunotherapy [6] Anthralin and diphenylcyclopropenone [6] Janus kinase (JAK) inhibitors [3,8,9] Ruxolitinib [8] Tofacitinib [3,9] Laser [10][11][12] 308-nm excimer laser [10] 908-nm diode laser [11] 1,550-nm fractional laser [12] Minoxidil [7] Photodynamic therapy [13] Platelet-rich plasma (PRP) [14] Prostaglandin F2-alpha analogues [7] Latanoprost [7] Treatment of concurrent Helicobacter pylori infection [4] Our patient decided to treat his beard alopecia areata with topical 0.1% triamcinolone acetonide cream. This led to a complete regrowth of his beard hair within six months.…”
Section: Treatment Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of case reports and one open-label, single-arm trial of ruxolitinib have been published ( Table 2 ). 10 , 50 , 68 73 Concerning oral ruxolitinib, Xing et al, apart from establishing the effects of JAKis in alopecic skin through in vivo study, had reported three cases of AA treated with 20 mg of oral ruxolitinib twice daily. 10 All three patients experienced near-complete regrowth within 3–5 months.…”
Section: Ruxolitinibmentioning
confidence: 99%
“…The development of the disease displays different courses to a great extent for patients, and the most prevalent for AA is the patchy type defined by oval areas of hair loss which is usually followed by spontaneous recovery. Alopecia totalis, one of the severe types of AA, causes complete loss of scalp hair while alopecia universalis leads to complete loss of scalp and body hair [5]. The chance of full recovery for alopecia totalis or universalis is lower than 10% [6].…”
Section: Introductionmentioning
confidence: 99%